Competitive Strategy Analysis and Formulation of Selected Strategy Alternatives Through the Blue Ocean Strategy Approach at PT XYZ - Heni Martanti; Ratri Wahyuningtyas (Pelopor Publikasi Akademika, 2024)
PT XYZ is a dairy manufacturing company in an industry that has high competition. Products from PT XYZ are not satisfactory even though the price is competitive, so they often do not reach sales and revenue targets. This research aims to find out the internal and external conditions of PT XYZ and formulate the right strategy to compete in the market. This study uses a qualitative method with a case study approach, collecting primary data through interviews, questionnaires, and observations, as well as secondary data from company literature and other sources. Sampling was carried out by the purposive sampling method and the validity of the data was checked using source triangulation. Data analysis was carried out using various matrices such as IFE, EFE, IE, SWOT, and QSPM, as well as blue ocean strategies for the implementation of the right strategy. The results of the study show that the IFE matrix score is 2.607 and the EFE matrix score is 3.435, so that the position of PT XYZ on the SWOT diagram in quadrant II. From the results of the SWOT matrix, the company has 11 alternative strategies, including 4 SO strategies, 2 ST strategies, 3 WO strategies, 2 WT strategies. An alternative strategy that is the main priority based on the eval_uation of the QSPM matrix is product innovation. The recommended strategy for PT XYZ to face competition is to innovate products. By developing new dairy products that have added value or new variants, PT XYZ can differentiate itself from competitors in the dairy market. These innovative products can attract the attention of consumers who are looking for variety or additional benefits from dairy products. Through this innovative product, PT XYZ can increase sales and expand the market.